2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279611
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Prevent the Negative Impact of the Metastable Defect in Boron Doped CZ Silicon Solar Cells

Abstract: A new reaction model concerning the boron-oxygen related degradation is presented, introducing a third recombination inactive state, that stabilizes the electrical parameters of Cz-Si solar cells, and the transition to this new inactive state is proven by experimental data. Furthermore, the stability under solar cell working conditions and the formation kinetics of this additional state are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 2 publications
(7 reference statements)
4
73
0
Order By: Relevance
“…As a consequence, the values for activation energy and characteristic frequency given here are to be considered as minimum, respectively maximum, values because the increase in defect concentration might be slightly accelerated due to degrada tion effects that are not caused by the destabilization of 80 related defects, e.g., degradation of the SiNx:H surface passivation layer. In fact, at least 20% of the defect concentration measured after the whole destabilization process is due to defects that cannot be rendered inactive by a typical 80 annealing treatment of 10 Hence, destabilization of 80 related defects in the dark is not going to pose a major problem during the lifespan of a typical solar cell, as al ready predicted by Herguth et al [25), especially as the solar cell only reaches higher temperatures around 60 oc by ilium ina tion which in turn most probably promote a slow regeneration neutralizing the destabilization effect.…”
Section: Thennal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the values for activation energy and characteristic frequency given here are to be considered as minimum, respectively maximum, values because the increase in defect concentration might be slightly accelerated due to degrada tion effects that are not caused by the destabilization of 80 related defects, e.g., degradation of the SiNx:H surface passivation layer. In fact, at least 20% of the defect concentration measured after the whole destabilization process is due to defects that cannot be rendered inactive by a typical 80 annealing treatment of 10 Hence, destabilization of 80 related defects in the dark is not going to pose a major problem during the lifespan of a typical solar cell, as al ready predicted by Herguth et al [25), especially as the solar cell only reaches higher temperatures around 60 oc by ilium ina tion which in turn most probably promote a slow regeneration neutralizing the destabilization effect.…”
Section: Thennal Stabilitymentioning
confidence: 99%
“…Herguth et al have shown that active BO related defects can be transformed into a recombination inactive state being stable under solar cell operating conditions by applying a regeneration procedure consisting of a combination of carrier injection and slightly elevated temperatures [10,11]. Recent results suggest that hydrogen might be the key factor to fast regeneration processes [12,13]: It has been shown, that if more hydrogen is introduced into the silicon bulk realized e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, both types of LID can be followed by subsequent regeneration of τ b [9]- [12] allowing for permanent curing of LID in the bulk. Once τ b is sufficiently high, surface passivation becomes the limiting factor and renders solar cells more susceptible to degradation of surface passivation.…”
Section: Introduction Lmentioning
confidence: 99%
“…5 The defect is dissociated at 200 C, 6 and the degradation can be prevented by simultaneous illumination and annealing. 7 Copper is a common 3d transition metal impurity in industrial silicon solar cells, which under illumination also causes lifetime degradation (Cu-LID). [8][9][10] Hence, crystalline silicon can suffer from BO-LID, Cu-LID, or a combination of both degradation effects.…”
Section: Introductionmentioning
confidence: 99%